An association of vertebral breast cancer metastasis and multiple myeloma, revealed by a spinal cord compression - Abdelhakim Kherfani; Khalil Amri; Mahjoub Hachem; Leila Abid; Mouna Bouaziz; Mondher Mestiri (The Pan African Medical Journal, 2014)

(untitled)
Authors describe the case of a patient with breast cancer and multiple myeloma as the second metachronous disease responsible for spinal cord compression. Synchronous occurrence of bone marrow breast cancer disease and multiple myeloma has not been described in the literature, as in this case. By presenting this case, we point to possible association between both diseases and the possible factors involved in the development of second malignant disease.